Effects of Ultraviolet C Irradiation on Stilbene Biosynthesis in Vitis vinifera L. cv. Cabernet Sauvignon Berry Skins and Calli - Xu, A.; Zhan, J.-C.; Huang, W.-D. (South African Journal of Enology and Viticulture, 2016)
Vitis vinifera L. cv. Cabernet Sauvignon berries and calli were irradiated with ultraviolet C (UV-C) to investigate the effects on the biosynthesis of stilbene. The stilbene content in the berry skins was enhanced significantly after 10 min of UV-C irradiation over the 24 h time course, and the results varied depending on the development stage of the fruit. The maximum production of total stilbene in the berry skins occurred at 12 h after treatment, with a content of 848.45 ± 23.53 μg/g fresh weight (FW) at the beginning of véraison, 591.77 ± 26.90 μg/g FW at the end of véraison, and 170.71 ± 6.85 μg/g FW at the ripening stage. Different UV-C dosages, from 5 to 30 min, induced stilbene accumulation considerably in the calli over the 120 h experimental period, and 20 min was the most efficient. The maximum of total stilbene accumulation in the calli was 125.07 ± 3.01 μg/g FW at 96 h after 20 min irradiation. Total phenolics and total flavonoid content increased after UV-C irradiation in both the berry skins and calli. The relative expression of genes encoding enzymes involved in the branching point of stilbene and flavonoid biosynthesis was up-regulated by UV-C irradiation. The results show that UV-C irradiation significantly promotes stilbene and flavonoid biosynthesis in grape berry skins and calli, and the induction effects depend on fruit development stage and UV-C dosage.